Uji Efektivitas Ekstrak Daun Cengkeh (Syzygium aromaticum L.) untuk Menghambat Pertumbuhan Colletotrichum sp. Penyebab Penyakit Antraknosa pada Buah Pepaya (Carica papaya L.) - FITRIANA, FIRA; SUDARMA, I MADE; SUNITI, NI WAYAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.11, No.4, Oktober 2022, 2023)
Effectiveness of Clove Leaf Extract ( Syzygium aromaticum L.) to Inhibit the Growth of Colletotrichum sp. Causes Anthracnose Disease on Papaya Fruit ( Carica papaya L.) Papaya ( Carica papaya L.) is a fruit that has high economic value. Papaya production in Indonesia fluctuates, one of which is due to anthracnose disease caused by Colletotrichum sp. Environmentally friendly controls that can be used are botanical fungicides. Clove leaf is a plant material that is antifungal. This study aims to determine the effectiveness of clove leaf extract to inhibit the growth of Colletotrichum sp. causes anthracnose on papaya fruit. This study used a completely randomized design. Inhibition test of clove leaf extract by colony method and MIC ( Minimum Inhibitory Concentration ) in vitro using extract concentration 0%; 0,1%; 0,2%; 0,3%; 0,4%; 0,5%; 0,6%; 0,7%; 0,8%; 0,9%; 1%; 2%; 3%; 4%; 5%. In vivo test of the effectiveness of clove leaf extract against Colletotrichum sp. on papaya fruit using extract concentration 0%; 1%; 2%; 3%; 4%; 5%. The results showed that clove leaf extract concentrations of 3%, 4%, 5% effectively inhibited the growth of Colletotrichum sp. with 100% inhibition and MIC value was 0,1%. In vivo results showed clove leaf extract with concentrations of 4% and 5% effectively inhibited Colletotrichum sp. colonies and suppressed infection on papaya fruit with the percentage of colony inhibition and fruit damage inhibition respectively 71,22%; 76,48% and 71,44%; 76,93%.